2011
DOI: 10.1210/en.2010-0716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Hyperphagic Response to Dietary Fat in the MC4R Knockout Mouse

Abstract: Defective melanocortin signaling causes hyperphagic obesity in humans and the melanocortin-4 receptor knockout mouse (MC4R(-/-)). The human disease most commonly presents, however, as haploinsufficiency of the MC4R. This study validates the MC4R(+/-) mouse as a model of the human disease in that, like the MC4R(-/-), the MC4R(+/-) mouse also exhibits a sustained hyperphagic response to dietary fat. Furthermore, both saturated and monounsaturated fats elicit this response. N-acylphosphatidylethanolamine (NAPE) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 38 publications
6
60
1
Order By: Relevance
“…For instance, the lower overall food intake appeared to be particularly driven by reductions in food intake during the dark phase (the active period), which was accompanied by shorter meal bouts and smaller meal size without an effect on intermeal intervals. This effect of pNAPE-EcN treatment on meal patterning for high-fat feeding differs somewhat from previous reports in chow-fed rats, in which increasing NAE levels decreased food intake primarily by increasing post-meal intervals and adiposity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Biosynthesis of small-molecule therapeutic compounds like NAPEs may have several potential advantages over biosynthesis of anorexigenic peptides or the use of nonmodified probiotic bacteria.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…For instance, the lower overall food intake appeared to be particularly driven by reductions in food intake during the dark phase (the active period), which was accompanied by shorter meal bouts and smaller meal size without an effect on intermeal intervals. This effect of pNAPE-EcN treatment on meal patterning for high-fat feeding differs somewhat from previous reports in chow-fed rats, in which increasing NAE levels decreased food intake primarily by increasing post-meal intervals and adiposity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Biosynthesis of small-molecule therapeutic compounds like NAPEs may have several potential advantages over biosynthesis of anorexigenic peptides or the use of nonmodified probiotic bacteria.…”
Section: Discussioncontrasting
confidence: 80%
“…After their synthesis, NAPEs are rapidly converted to the active NAEs through hydrolysis by NAPEhydrolyzing phospholipase D (NAPE-PLD). Intraperitoneal administration of NAEs, where the N-acyl chains are saturated or monounsaturated (e.g., N-oleoyl-ethanolamide [OEA]), or of their precursors (e.g., C16:0NAPE) markedly reduces food intake and obesity in mice fed a high-fat diet (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Chronic NAE administration appears to modulate adiposity through multiple mechanisms including inhibition of fat absorption (25), delayed gastric emptying (26,27), reduced food intake (19,20,28,29), and increased fatty acid oxidation (23,25).…”
Section: Introductionmentioning
confidence: 99%
“…Having shown that MC4R deficiency confers reduced dietary preference for sucrose-rich food, we sought to test whether MC4R deficiency causes dietary fat preference consistent with the high-fat hyperphagia noted previously (15,16). To study these feeding behaviors, we used groups of WT, MC4R…”
Section: Mc4r −/− Mice Exhibit Low Preference For Palatable High-fat mentioning
confidence: 99%
“…5A). Following the initial period of novelty associated with the HFD presentation, all groups reached a steady level of intake of both SC and HFD by the second week of the two-choice diet (days [16][17][18][19][20][21][22]. The intake levels for both diets also remained unchanged after the position of each was switched (days 23-25), suggesting that the feeding preferences are not dependent upon location of the diets within the cage (Fig.…”
Section: Mc4r −/− Mice Exhibit Low Preference For Palatable High-fat mentioning
confidence: 99%
See 1 more Smart Citation